Mitochondrial genome sequencing of the monogenean Heterobothrium okamotoi isolated from the tiger puffer Takifugu rubripes in North China. Issue 2 (3rd July 2019) - Li, Ruijun; Zhou, Cheng; Ye, Shigen; Men, Lei; Liu, Ying; Fu, Songzhe
Abstract: In this study, monogenean Heterobothium okamotoi was isolated and identified from the gill of diseased Tiger puffer ( T. rubripes ) at an industrial farm in Liaoning, North China (121.3459 E, 38.9861 N). With the completion of H. okamotoi mitochondrial genome sequencing, the full-length mitochondrial genome of H. okamotoi was assembled and analyzed. All results indicate that the complete mitochondrial genome of H. okamotoi was 14, 643 bp. There were 2 rRNAs, 20 tRNAs, and 12 protein-coding genes (PCGs) all located at the heavy (H) strand. Besides, the phylogenetic tree of 19 monogeneans was constructed. The results showed that H. okamotoi and Pseudochauhanea macrorchis were clustered in a clade. To sum up, our research results would further provide essential data for systematics and evolution study of H. okamotoi .